2002
DOI: 10.1197/jamia.m1089
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Medical Learning Environments on the Internet

Abstract: Learning anatomy and surgical procedures requires both a conceptual understanding of three-dimensional anatomy and a hands-on manipulation of tools and tissue. Such virtual resources are not available widely, are expensive, and may be culturally disallowed. Simulation technology, using high-performance computers and graphics, permits realistic real-time display of anatomy. Haptics technology supports the ability to probe and feel this virtual anatomy through the use of virtual tools. The Internet permits world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Recent studies support what is commonly experienced: students have difficulties achieving a conceptual understanding of 3D anatomy based on abstract teaching (Cottam 1999;Miller 2000;Garg et al 2001;Dev et al 2002). Misconceptions about physiological phenomena are persistent and hard to address in education (Michael 1998(Michael , 2002.…”
Section: Specific Educational Problems Concerning Anatomy and Physiologymentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies support what is commonly experienced: students have difficulties achieving a conceptual understanding of 3D anatomy based on abstract teaching (Cottam 1999;Miller 2000;Garg et al 2001;Dev et al 2002). Misconceptions about physiological phenomena are persistent and hard to address in education (Michael 1998(Michael , 2002.…”
Section: Specific Educational Problems Concerning Anatomy and Physiologymentioning
confidence: 89%
“…More recently, information technology (IT), and in particular 3D visualization, has improved the possibilities for students to imagine hidden structures and functions, thereby facilitating understanding of complex phenomena. The usefulness of 3D images is well documented (Rosse 1995;Zirkel & Zinkel 1997;Garg et al 2001;Dev 2002;McLachlan et al 2004). Simplification, in order to support student learning, might lead to misconceptions and misunderstandings that are hard to let go (Spiro et al 1989).…”
Section: Specific Educational Problems Concerning Anatomy and Physiologymentioning
confidence: 91%
“…The virtual cadaver presented through a variety of media was the new method to promote the quantitative optimum of the anatomy knowledge. Learning anatomy and surgical procedures requires both a conceptual understanding of three-dimensional anatomy and a hands-on manipulation of tools and tissue (Dev et al;Theodoropoulos et al, 1994). There is a remarkable growth in the interest and use of multimedia programs besides the growth in skill in developing multimedia programs.…”
Section: Discussionmentioning
confidence: 99%
“…They praise the need for the given topics and for more integration with the relevant clinical courses (Abutarbush et al, 2006). Individual differences in approaches to learning, prior knowledge and levels of interest lead students to approach an anatomical problem in a variety of ways, which support higher levels of cognition, including reflective thinking (Croy & Dobson, 2003;Dev et al, 2002;Josephson & Moore, 2006;Khalil et al, 2005a;Laurillard, 2013;Linton et al, 2005;Perry et al, 2007;Ramsden, 2003). Evaluation studies have also demonstrated the potential of e-learning for the enhancement of students' professional skills (Abutarbush et al;Khalil et al, 2005a;Wilkes & Bligh, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Touch and kinaesthetic sensation through feeling and manipulating real human tissues is available through studying cadavers, prosected specimens, and living human models (McLachlan and Patten, 2006;Dev et al, 2002), and is particularly important for surgical and procedural training (Dev et al, 2002). Thus, adding haptic feedback to CAL resources has been an active area of research and development for two decades, including for surgical training (Hoffman and Vu, 1997;Dev et al, 2002;Panait et al, 2009;Fang et al, 2014;Ruthenbeck and Reynolds, 2015;Basdogan et al, 2004;Esteban et al, 2014;Kim et al, 2013;Schvartzman et al, 2014;Thomas, 2013;Wu et al, 2014), clinical procedural training (Arevalo et al, 2013), palpation training (Howell et al, 2008;Ullrich and Kuhlen, 2012), and anatomical education (Dev et al, 2002;Kinnison et al, 2009;Sakellariou et al, 2009;Ingole et al, 2015;Khot et al, 2013;Lewis et al, 2014a;Weber et al, 2012).…”
Section: Introductionmentioning
confidence: 99%